Early prediction of lenvatinib treatment efficacy by using 18F-FDG PET/CT in patients with unresectable or advanced thyroid carcinoma that is refractory to radioiodine treatment: a protocol for a non-randomized single-arm multicenter observational study. Issue 8 (30th August 2018) - Takeuchi, Satoshi; Shiga, Tohru; Hirata, Kenji; Taguchi, Jun; Magota, Keiichi; Ariga, Shin; Gouda, Tomohiro; Ohhara, Yoshihito; Homma, Rio; Shimizu, Yasushi; Kinoshita, Ichiro; Tsuji, Yasushi; et al.
Abstract : Introduction: Lenvatinib, an oral molecular targeted drug, is used to treat patients with unresectable or advanced thyroid carcinoma that is refractory to radioiodine treatment. Effective methods for evaluating molecular targeted drugs are a critical unmet need owing to their expensive costs and unique adverse events. The aim of this study is to determine whether 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/CT at 1 week after commencing lenvatinib can predict treatment outcomes. Design and methods: This study is planned as a non-randomised single-arm multicentre study; patients with pathologically confirmed differentiated thyroid carcinoma (DTC) with lesions that are refractory to radioiodine treatment are eligible. The main exclusion criteria are medullary or anaplastic carcinoma, prior treatment with chemotherapy, poor general condition and thromboembolism-requiring treatment. Patients to be included in the study will be treated with lenvatinib and undergo FDG-PET/CT examination twice: before and 1 week after the initiation of treatment. Contrast-enhanced CT, the gold standard for evaluation, will be performed at least 4 weeks after the initiation of treatment. The primary objective is to evaluate the ability of the lesion maximum standard uptake value for FDG PET/CT performed 1 week after the initiation of treatment to predict outcomes compared with the response evaluation obtained via contrast-enhanced CT performed at least 4 weeks after the initiation of treatment. Ethics and dissemination: This study is conducted in accordance with the Declaration of Helsinki and has received ethical approval from the institutional review board of the Hokkaido University Hospital (approval number: 015-402). The results of this study will be disseminated through a presentation at a conference and the publication of the data in a peer-reviewed journal. The study will be implemented and reported in line with the SPIRIT statement. Trial registration number: UMIN000022592.